The SENECA study: Prognostic role of serum biomarkers in older patients with metastatic colorectal cancer. Issue 8 (November 2020) - Lisanti, Camilla; Basile, Debora; Parnofiello, Annamaria; Bertoli, Elisa; Andreotti, Victoria Josephine; Garattini, Silvio Ken; Bartoletti, Michele; Cattaneo, Monica; Di Nardo, Paola; Bonotto, Marta; Casagrande, Mariaelena; Da Ros, Lucia; et al.
Abstract: Background: Aging induces meaningful changes in the immune system and inflammation response with increase in monocyte-lymphocyte ratio (MLR) and serum lactate dehydrogenase (LDH) levels. Aim of this study was to explore the prognostic role of MLR and LDH levels in older patients (pts) with metastatic colorectal cancer (mCRC). Methods: We conducted a retrospective analysis of a consecutive cohort of 168 older (>70 years) patients with mCRC. The prognostic impact of MLR and LDH levels on overall survival (OS) was investigated through uni-and multivariate Cox regression analyses. Moreover, we categorized patients into three groups according to MLR and LDH levels (group 1: MLR-low and LDH-low; group 2: MLR-high or LDH-high; group 3: MLR-high and LDH-high). Results: By univariate analysis, high LDH level (HR 1.74, 95% CI 1.05–2.90) and high MLR level (HR 2.19, 95% CI 1.48–3.44) were significantly associated with a worse OS. Conversely, primary tumor resection and left-sidedness were significantly associated with a longer OS. By multivariate analysis, high LDH level (HR 2.00, 95% CI 1.13–3.55) and high MLR level (HR 2.99, 95% CI 1.68–5.33) were independent prognostic factors of worse prognosis. Compared to group 1, a shorter survival was reported for patients included in group 2 (HR 1.97, 95% CI 1.21–3.23 in univariate; HR 2.54, 95% CI 1.43–4.51 in multivariate) or in group 3 (HR 2.42, 95% CI 24–4.74, p  = .010 in univariate; HR 5.59, 95% CI 2.15-14.54 in multivariate) Conclusions: High baseline levels of LDH, MLR or both are independent unfavorable prognostic factors in older patients treated with first-line chemotherapy for mCRC.